Government Policies In Increasing Post-Covid-19 Economic Growth In Indonesia - Etika Khairina; Mochammad Iqbal Fadhlurrohman; Mohammad Eisa Ruhullah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
During the COVID-19 pandemic, the economy experienced little due to the absence of economic activities. The economic slowdown will result in a financial crisis, so the Indonesian government must immediately address the problem. This study will carry out the economic process in Indonesia after the outbreak to achieve financial balance. This study uses a qualitative approach. Data is obtained through secondary data such as social media, mass media, and data issued by the government for analysis using variables and indicators from previous theories. The study was carried out using the triangulation technique and data analysis software, namely, Nvivo 12 Plus data analysis. The data collection will then be reviewed based on the data analysis program and display the results in visible effects of the software. This study uses various variables in economic development, such as infrastructure, natural resources, human resources, micro, small and medium enterprises (MSMEs), and digitalization. The most essential, significant efforts to increase economic development are held by infrastructure, which accounts for 86% of the total. Efforts to reduce the unemployment rate until 2022 have not been too significant.